Situated learning in the mobile age: mobile devices on a field trip to the sea - Vanessa D.I. Pfeiffer; Sven Gemballa; Halszka Jarodzka; Katharina Scheiter; Peter Gerjets (Association for Learning Technology, 2009)
This study focuses on learning about fish biodiversity via mobile devices in a situated learning scenario. Mobile devices do not only facilitate relating the presented information to the real world in a direct way; they also allow the provision of dynamic representations on demand. This study asks whether mobile devices are suited to support knowledge acquisition in a situated learning scenario and whether providing dynamic content is an additional benefit of mobile devices in combination with a real-world experience. The study was conducted during a regular university course at the Mediterranean Sea. Students had to acquire knowledge on 18 Mediterranean fish species by using either static (n = 16) or dynamic learning materials (n = 17). An initial classroom activity was followed by a real-world experience with mobile devices (snorkelling activity). Learning outcomes were measured before and after snorkelling. A 2×2 mixed ANOVA revealed that students performed better after than before the mobile learning experience, whereas no main effect for learning material could be found. However, an interaction between both factors indicated that the knowledge gain in the dynamic group exceeded the knowledge gain in the static group. These results indicate that mobile devices are helpful to unfold the potential of dynamic visualisations for learning biodiversity in a situated learning scenario.